SISTEM MONITORING KETINGGIAN AIR DAN OTOMASI PENGHIDUPAN LAMPU PADA BUDIDAYA HIDROPONIK BERBASIS IOT - AHMAD ZATNIKA PURWALAKSANA (LP2MTBM MAKARIOZ, 2020)
Increasing the number of population and the large number of convertion to non-agricultural land has caused problems inthe supply of food especially in agriculture. Hydroponics is the solution to that problem. Hydroponics has some advantagethat the cultivation can be done in a narrow aren a, it does not use soil media for plant growth, and the quantity and qualityof harvest is higher. In hydroponics, there are several parameters that must be controlled, some of which are water leveland lighting. In this research, a water level monitoring system has been made using an ultrasonic sensor hc-sr04 and theautomation of the lighting is using a Light Dependent Resistor (LDR) sensor and growing plant lamp. All sensors andactuators are integrated with Raspberry pi. By applying IoT (Internet of Things) technology, the Cayenne platform is usedso that data can be accessed by users from anywhere via the internet with the aim of minimizing hydroponic maintenancemanually and producing smart hydroponic systems based on IoT.